STUDY OF ACCESSORY FORAMEN TRANSVERSARIA IN CERVICAL VERTEBRAE - Rathnakar, Pretty; K., Remya; Swathi (Journal of Health and Allied Sciences NU, 2013)
The cervical vertebrae presents foramen transversaria in each transverse process. In all but the seventh cervical vertebra, the foramen normally transmits vertebral artery and vein and a branch from the cervicothoracic ganglion.140 cervical vertebrae were studied. Variations were noticed in the number of foramen transversarium unilaterally and bilaterally. Variations in foramen transversarium may indicate the variation in course of vertebral arteries
Keywords: Foramen transversaria; cervical vertebra; vertebral artery